2017
DOI: 10.1016/j.ijpsycho.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the possible mechanisms of blunted cardiac reactivity to acute psychological stress

Abstract: Blunted cardiovascular reactivity to acute psychological stress has been linked to a range of adverse health and behavioral outcomes. However, the origins of blunted reactivity remain unclear. The current study aimed to explore the following possibilities: different appraisals of task stressfulness and/or difficulty, diminished task effort, or reduced physiological capacity to respond. Individuals characterized, via pre-screening, as blunted (n=17) or exaggerated (n=16) heart rate (HR) reactors to acute psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…In addition, the present study extends the current literature by demonstrating the reactivity‐perseverance relationship in response to multiple stress tasks, including a passive psychological stressor (i.e., the cold pressor task). However, these cold pressor effects were less evident after adjustment for potential confounding variables, perhaps providing further evidence that blunted reactivity among certain individuals is more likely to be apparent in response to active stress, as observed previously (Brindle et al, ). In addition, much of the previous reactivity‐perseverance research has centered around cessation and the ability to persevere by refraining from unhealthy addictive behavior choices.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the present study extends the current literature by demonstrating the reactivity‐perseverance relationship in response to multiple stress tasks, including a passive psychological stressor (i.e., the cold pressor task). However, these cold pressor effects were less evident after adjustment for potential confounding variables, perhaps providing further evidence that blunted reactivity among certain individuals is more likely to be apparent in response to active stress, as observed previously (Brindle et al, ). In addition, much of the previous reactivity‐perseverance research has centered around cessation and the ability to persevere by refraining from unhealthy addictive behavior choices.…”
Section: Discussionsupporting
confidence: 78%
“…This may reflect social desirability bias for the Grit-S scale (Bazelais, Lemay, & Doleck, 2016;Duckworth, Peterson, Matthews, & Kelly, 2007), the neglect of measuring important mediators between self-report and behavioral measures, or that behavioral perseverance assessments examine state whereas self-report questionnaires assess trait perseverance (Steinberg & Williams, 2013). On the other hand, this lack of association may be consistent with the more interesting finding that blunted responders are not consciously aware of deficiency in their motivation (Brindle et al, 2017) and do not self-report differences in task engagement or performance markers of effort, in comparison to those displaying higher cardiovascular reactivity (Brindle et al, 2017;Ginty et al, 2012). This would suggest that self-report measures of perseverance are not useful in determining perseverance/relapse in real-world situations, for example, during addiction cessation or dietary programs.…”
Section: Discussionmentioning
confidence: 87%
“…Passive tasks can further be considered as physical or psychological stressors. For example, within the cardiovascular reactivity literature a common passive stressor is the cold pressor task (e.g., Brindle, Whittaker, Bibbey, Carroll, & Ginty, 2017;Tuomisto, Majahalme, Kahonen, Fredrikson, & Turjanmaa, 2005;Vella & Friedman, 2007). However, even though employed as a psychological stressor, this task involves physical changes, and might better be regarded as a physical stressor.…”
Section: Introductionmentioning
confidence: 99%
“…This finding reflects the findings by Lee and Hughes (), which showed no significant interaction between subjective task ratings and dominance but is in contrast to previous work, which found increased CVR for high dominant participants, and this increase was interpreted as indicative of greater effortful coping attempts (see Gramer & Berner, ). Previous work has reported that individuals with characteristically blunted stress responses do not report significantly different subjective stress or task difficulty from those with exaggerated stress responses (Brindle, Whittaker, Bibbey, Carroll, & Ginty, ). This lends some support to an explanation of the results as not being due to diminished task effort or reduced engagement by those higher in dominance and attributes the source of difference between groups to their differential, characteristic cardiovascular responses.…”
Section: Discussionmentioning
confidence: 88%